Sistema de informações geográficas de desastres naturais no Estado do Amapá - SANTOS, Carla de Mattos (2019)
The occurrence of natural disasters is a risk when human presence in affected areas. Over the past years, these events are more frequently in Amazonia, in both urban and rural areas. Therefore, is necessary to adopt precautionary and mitigation actions aiming to avoid major problems. Nevertheless, the risk management composes an important factor to reduce possible damages and losses caused by disasters. The combination of knowledge of morphology and social aspects of risky areas is critical on decision making process referring to implementation of public policies that allow the reduction or controls the risks, changing the probabilities of occurrence and managing the consequences. This paper aims to classify the susceptibility of natural disaster risks in Amapa State, according to local geological recognition and detailed information regarding vulnerable flood areas, erosion and mass movement, as well as the rating of social vulnerability in the areas of Ferreira Gomes, Laranjal do Jari and Vitoria do Jari.